Investigating the relationship between emotional intelligence and shooting scores among the military staff - ali roshandel hesari; Mohammad Hosein Daneshi Nejad (فصلنامه ابن سینا)
Background: The shooting and accuracy of doing it is one of the most important concerns of military personnel and commanders. This study was designed to investigate emotional intelligence, its relationship with the shooting scores of the military staff, and also determining the components of emotional intelligence that can predict the shooting scores. Materials and methods: The research method was correlation type and 104 staff members if Nezaja were randomly selected for the study (according to the companies and educational level). To collect information about emotional intelligence, the standard Bar-On's questionnaire was used after validation by relevant field experts. Reliability of the questionnaire was confirmed by Cronbakh's alpha. The collected data were analyzed by SPSS software. Pearson's correlation and regression were used to measure the relationship and predictive factors, respectively. Results: The results showed a positive and significant relationship between emotional intelligence and shooting scores (r=0.411, p<0.05). Among the components of emotional intelligence, stress tolerance, impulse control, emotional self-awareness, problem solving, and self-actualization had the most role in predicting the shooting scores. Conclusion: Therefore, paying attention to the features and factors of emotional intelligence can be helpful in improving the shooting scores of military personnel.